(untitled) (Global Journal of Human-Social Science, 2025)
This article analyzes the imperative of integrating socioemotional competencies into legal education, in response to a global demand aligned with benchmarks such as UNESCO’s 21st-century competencies and Sustainable Development Goal 4 (SDG 4). It critiques the limitations of traditional, technically focused legal pedagogy and advocates for transformative approaches that combine active methodologies with interdisciplinary rigor to better teach socioemotional competencies to law students. Through case studies from U.S. law schools, the study demonstrates how curricula emphasizing self-awareness, empathy, and strategic communication produces jurists capable of addressing contemporary legal challenges while upholding ethical and humanistic values. The analysis underscores the need for pedagogical reforms that align legal training with the socioemotional demands of modern practice, fostering professionals equipped to navigate complexity with both technical mastery and emotional intelligence.